Kualitas Pelayanan Publik pada Badan Penyelenggara Jaminan Sosial Ketenagakerjaan Tanjung Perak - Loktavia Rosanjaya; Binti Azizatun Nafi'ah (UIR Press, 2023)
The purpose of this study is to find out how the quality of service delivery provided by BPJS Ketenagakerjaan Tanjung Perak. This research is a qualitative type of research which uses a descriptive approach as a research method. Observation, documentation, and interviews are used as data collection methods in this study, so that after the research data is obtained, the next process of data analysis uses the stages of reducing the data that has been obtained, presenting data, and drawing conclusions. The subjects of this study are participants and prospective participants who have received services from BPJS Ketenagakerjaan Tanjung Perak. From the results of the research that has been conducted, it shows that the quality of public services at BPJS Ketenagakerjaan Tanjung Perak has been carried out well as a whole, where it has fulfilled five dimensions in the implementation of public service quality which are studied through the dimension of reliability, dimension of responsiveness, dimension of assurance, dimension of empathy, and dimension of tangible.